Knowledge, attitude and practices about menopause and menopausal symptoms among midlife school teachers - Sultan, Shabana; Sharma, Amita; Jain, Nitin Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study is aimed towards women’s knowledge and attitudes towards menopause as menopause brings multifaceted impact including psychomotor, vasomotor and cardiovascular changes on women`s health. Methods: The population of interest consisted of 150 qualified teachers of age group 40 to 60 years and above from different colleges and schools of Bhopal city. The data was collected using predesigned questionnaire with inform consent and responses were analysed using simple percentages. Results: In this study, mean age of menopause is 48.4 years and 92% of women had knowledge about menopause out of them 84% of women consider it to be a natural process. Working capacity of 66% of the women was affected while sexual life is affected in 56% of the women. 88% of the women were aware of hormonal replacement therapy but only 4.6% of women were taking HRT due to concerns regarding side effects. Conclusions: Most of the women in our study are aware of menopause and its symptoms but they are not following healthy life style modifications. Increased awareness is required to prepare women for menopause.